The Effect of Liquidity and Working Capital Turnover on Profitability at PT. Sumber Cipta Multiniaga, South Jakarta - Jasmani, Jasmani (Universitas Negeri Makassar, 2019)
The logical consequence of credit sales is the increase in trade receivables which in turn disrupts the company's liquidity. Â This study aims to determine the effect between liquidity and working capital turnover on profitability at PT. Sumber Cipta Multiniaga. The method uses survey techniques and saturated sampling in the form of financial statements. The analytical tool used is descriptive and verification analysis with assumptions with statistical analysis in the form of regression tests, correlation coefficient tests, determination coefficient tests and hypothesis tests. The results of the current ratio study have a significant effect on the determination of 32.6%. Hypothesis testing obtained Ï value 0,000 <0.05. Working capital turnover has a significant effect on return on assets, with a determination of 29.6%. Hypothesis testing obtained Ï value 0,000 <0.05. The current ratio and Working capital turnover simultaneously have a significant effect on the return on assets with a determination of 49.2%. Hypothesis testing obtained Ï value 0,000 <0.05.